Does Mandatory Adoption of International Financial Reporting Standards Decrease the Voting Premium for Dual-Class Shares? - Hong, Hyun A. (The Accounting Review, 2013)
ABSTRACT I examine whether voting premiums are reduced following mandatory International Financial Reporting Standards (IFRS) adoption for firms that have a dual-class share structure. I find that mandatory adopters' voting premiums decrease, on average, by 8 percent subsequent to mandatory IFRS adoption. This effect is statistically significant relative to the corresponding effect for non-IFRS adopters. Further, I find that this effect is more pronounced in countries with strong legal enforcement and for mandatory adopters that experience an increase in the transparency and comparability of reported information under the new accounting regime. Taken together, these results support the view that mandatory IFRS adoption benefits minority shareholders by providing an effective mechanism to constrain the private benefits of control. However, one should interpret these results with caution as concurrent efforts to strengthen corporate governance regimes and the enforcement of corporate and securities laws may also contribute to the decrease in voting premiums documented in this paper. Data Availability: Data used in this study are available from the sources listed in the text.